2013
DOI: 10.1002/ajh.23560
|View full text |Cite
|
Sign up to set email alerts
|

Significance of deeper molecular responses in patients with chronic myeloid leukemia in early chronic phase treated with tyrosine kinase inhibitors

Abstract: Most patients with chronic myeloid leukemia (CML) in chronic phase (CP) treated with tyrosine kinase inhibitors (TKI) achieve complete cytogenetic response (CCyR). An increasing number of patients also achieve deep molecular responses (MR). We determined the frequency and significance of deep MR after TKI therapy for CML in CP. MR included: major molecular response (MMR), MR4, MR4.5, and undetectable transcripts (UND), ie BCR-ABL/ABL of ≤0.1%, ≤0.01%, ≤0.0032%, and undetectable transcripts, respectively. 483 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 29 publications
0
54
0
1
Order By: Relevance
“…Thus far, there is little evidence of a statistically significant improvement in overall survival (OS), though long-term follow up confirmed a superior rate of freedom from progression compared with patients with less deep molecular responses at the same time points. 8 The advent of TKIs in the treatment of CML has opened a new era of precision medicine for diverse malignancies in which relatively non-specific and often toxic drugs are gradually being replaced by safer and better tolerated agents whose mechanism of action is precisely defined, and for which the treatment algorithm is guided by individual patient genomic information. 9 Indeed, many TKIs have activity against other tyrosine kinases and could, therefore, be useful in treating patients whose malignancies harbor these gene mutations.…”
mentioning
confidence: 99%
“…Thus far, there is little evidence of a statistically significant improvement in overall survival (OS), though long-term follow up confirmed a superior rate of freedom from progression compared with patients with less deep molecular responses at the same time points. 8 The advent of TKIs in the treatment of CML has opened a new era of precision medicine for diverse malignancies in which relatively non-specific and often toxic drugs are gradually being replaced by safer and better tolerated agents whose mechanism of action is precisely defined, and for which the treatment algorithm is guided by individual patient genomic information. 9 Indeed, many TKIs have activity against other tyrosine kinases and could, therefore, be useful in treating patients whose malignancies harbor these gene mutations.…”
mentioning
confidence: 99%
“…With 5 years of follow-up in ENESTnd, 54% of patients in the nilotinib 300-mg twice-daily arm achieved MR 4.5 and 96% of patients had freedom from progression to AP/BC (vs. the imatinib arm: 31% [P < 0.0001] and 92% [P 5 0.0403], respectively) [16]. Retrospective landmark analyses of other independent clinical trials have demonstrated similar associations between deeper molecular responses and improved OS, event-free survival, and failure-free survival [20,29,35]. For example, patients who achieved a confirmed MR 4.5 at 4 years on frontline imatinib in the German CML IV trial had significantly higher OS at 8 years than patients who did not achieve this level of stable molecular response [20].…”
Section: Importance Of Achieving Deep Molecular Responses To Tki Therapymentioning
confidence: 97%
“…Thus, ELN recommends use of the term molecularly undetectable leukemia, together with the number of control gene transcripts, over the term CMR [11]. A response of MR 4.5 is easier to standardize than undetectable leukemia and represents a deep, measurable level of molecular response with similar clinical relevance [29]; for these and other reasons, MR 4.5 is a common criterion for TFR studies.…”
Section: Monitoring Molecular Responses To Tki Therapymentioning
confidence: 99%
“…[11] A separate study found a correlation between achievement of undetectable disease (assay sensitivity: 1 BCR-ABL1 transcript in 100,000 ABL1 copies; equivalent to MR 5 on the IS) and transformation-free survival and OS (versus patients with BCR-ABL1 IS 0.1%) on imatinib, nilotinib, or dasatinib therapy. [38] In the German CML-IV study, there was a correlation between achievement of MR 4.5 and OS in patients treated with imatinib, and no patient who achieved MR 4.5 had progressed after a median followup of 3 years. [10] In addition, several treatment-free remission studies have been initiated in patients following treatment with imatinib and second-generation TKIs, with stringent molecular response criteria for eligibility.…”
Section: Molecular Monitoring In Cml: Importance and Current Recommenmentioning
confidence: 99%